Add fuel to the fire: Inflammation and immune response in lung cancer combined with COVID-19 - Ai, Yanling; Wang, Hengyi; Zheng, Qiao; Li, Songtao; Liu, Jingwen; Huang, Ju; Tang, Jianyuan; Meng, Xiangrui (Frontiers in Immunology, 2023)
The corona virus disease 2019 (COVID-19) global pandemic has had an unprecedented and persistent impact on oncological practice, especially for patients with lung cancer, who are more vulnerable to the virus than the normal population. Indeed, the onset, progression, and prognosis of the two diseases may in some cases influence each other, and inflammation is an important link between them. The original chronic inflammatory environment of lung cancer patients may increase the risk of infection with COVID-19 and exacerbate secondary damage. Meanwhile, the acute inflammation caused by COVID-19 may induce tumour progression or cause immune activation. In this article, from the perspective of the immune microenvironment, the pathophysiological changes in the lungs and whole body of these special patients will be summarised and analysed to explore the possible immunological storm, immunosuppression, and immune escape phenomenon caused by chronic inflammation complicated by acute inflammation. The effects of COVID-19 on immune cells, inflammatory factors, chemokines, and related target proteins in the immune microenvironment of tumours are also discussed, as well as the potential role of the COVID-19 vaccine and immune checkpoint inhibitors in this setting. Finally, we provide recommendations for the treatment of lung cancer combined with COVID-19 in this special group.